PENDIDIKAN KARAKTER JUJUR PERSPEKTIF SIRAH NABAWIYAH: HONEST CHARACTER EDUCATION FROM THE PERSPECTIVE OF SIRAH NABAWIYAH - Mustakim, Iqbal; Hakim, Lukman Nul; Munir (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
Character education is a key factor in the process of achieving educational goals, which is influenced by a number of interrelated factors. The essence of a person's goodness is represented by his or her character. An educated individual should be morally upright, following in the footsteps of Prophet Muhammad (Sallahu' alaihi Wassalam), the greatest human role model. Students can develop a strong moral character by modeling his admirable qualities. An important part of achieving the goal of education, which is affected by a variety of closely related issues, is character education. A person's environment determines his or her goodness. Any individual seeking knowledge must treat others with dignity, act morally, and adhere to the teachings of Prophet Muhammad (Sallahu' alaihi Wassalam). By modeling his own good behavior, students can grow in moral character.